GENOMIC INTERACTIONS IN SKY: CHILDREN OF THE LIGHT VIDEO GAME - Hanifa Oktavia Salsabila; Diva Salsabila Septi Dewantari; Dzulfiqar Faris Al-faruq; Malika Ghania Gunawan (IAIN Surakarta, 2026)
This study investigates how avatar-mediated communication is structured and negotiated in digital game environments. Focusing on Sky: Children of the Light, this study examines genomic interactions through different avatar types that shape communication patterns. Grounded in Prosthetic Communication Ethnography, avatars are understood as prosthetic selves that mediate interaction through both verbal and non-verbal means. Using a descriptive qualitative approach with Spradley's ethnographic analysis, data were collected through non-participant observation, in-game screenshots, and gameplay videos. Findings reveal three avatar types, gamer-centric, game-centric, and gaming-centric, each corresponding to distinct genomic interaction patterns, free, restrictive, and progressive communication, respectively. Gamer-centric avatars enable player-driven non-verbal expression; game-centric avatars operate under system-controlled restrictions; and gaming-centric avatars unlock communication progressively through social bonding mechanics. These findings show that communication in the game is shaped by the interaction between player agency, system design, and social relationships, providing empirical insight into how genomic interaction operates within a system-mediated communication environment.